ANALISIS PERBANDINGAN INDEKS HARGA SAHAM GABUNGAN PADA BURSA EFEK INDONESIA SEBELUM DAN SESUDAH PANDEMI COVID-19 - Aminda, Renea Shinta; Susilo Nugroho; Raden Muhammad Jiddan Aziz; Raden Hurryaturohman; Jani subakti (Media Ekonomi, 2022)
The capital market is one of the long-term financial instrument trading platforms in a country in carrying out its function, which is to attract investors to invest. The growth of the Indonesian capital market is expected to continue to be positive and sustainable with transparent information. The development of information regarding the COVID-19 pandemic which first appeared in China had an impact on its economic sector. The corona virus has spread throughout the world including Indonesia, the emergence of cases of transmission and the number of victims that continues to increase has an impact on weakening people's purchasing power. This study used the Paired Sample T-test and Normality method with SPSS 23. The period used was monthly, starting from May 2018 to October 2020 before and after the pandemic case occurred. The first data analysis used was the normality test with the Shapiro-Wilk test approach. Based on the results of the research and discussion conducted, it can be seen that there is a significant difference from the value of the Indonesian Composite Stock Price Index for the last 15 months which shows positive and significant results where the hypothesis test accepts the hypothesis Ha and rejects H0. These results are in line with research conducted by previous researchers before and after the COVID-19 pandemic.